HERBAGE AND ESSENTIAL OIL YIELD OF OCIMUM SPP. INTERCROPPED UNDER PONGAMIA PINNATA BASED SILVIMEDICINAL SYSTEMS IN GUJARAT, INDIA - ANILKUMAR H. SUVERA; N. S. THAKUR; S. K. JHA (The Bioscan, 2015)
Present investigation was carried out in ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat, India. Four Ocimum species namely O. sanctum, O. tenuiflorum, O. basilicum and O. gratissimum were intercropped under 2.5 years old Karanja (Pongamia pinnata) based agroforestry systems named as silvi-medicinal system (Pongamia+Ocimum spp.) and sole cropping system following Factorial Randomized Block Design with three replications. Significantly higher fresh above and below ground and total herbage and oil yield of Ocimum spp. was recorded under silvi-medicinal systems compared to sole cropping. Out of four Ocimum species, maximum values of fresh above ground (10.54 t/ha) and total herbage yield (12.05 t/ha) were attained by O. tenuiflorum. Whereas, maximum below ground fresh herbage yield (20.08 t/ha) was recorded for O. basilicum. Among intercrops, significantly maximum oil yield (61.32 kg/ha) was obtained for O. tenuiflorum. The findings suggested that higher fresh herbage and oil yield can be achieved under silvi-medicinal systems (Karanja + Ocimum spp.) compared to sole cropping.